Pengembangan Kepercayaan Diri Siswa Kelas XI SMK Arinda Palembang melalui Latihan Pidato - Joni Iskandar; Margareta Andriani; Nur Atikah (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2025)
Community service activities (PkM) held by the Indonesian Education Study Program, Bina Darma University aim to increase the confidence of grade XI students of SMK Arinda Palembang through speech training. Speech is a public speaking skill that is very important in education and career. In this program, students are given a basic understanding of speech, then practice composing and delivering it, and are evaluated to measure the development of their abilities. As a result, students showed an improvement in confidence and communication skills after participating in this training. It is hoped that this activity can prepare students to face challenges in the world of work that require good presentation skills.